2011
DOI: 10.1021/la200751m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Roughness on Cetyltrimethylammonium Bromide Adsorption from Aqueous Solution

Abstract: The influence of surface roughness on surfactant adsorption was studied using a quartz crystal microbalance with dissipation (QCM-D). The sensors employed had root-mean-square (R) roughness values of 2.3, 3.1, and 5.8 nm, corresponding to fractal-calculated surface area ratios (actual/nominal) of 1.13, 1.73, and 2.53, respectively. Adsorption isotherms measured at 25 °C showed that adsorbed mass of cetyltrimethylammonium bromide per unit of actual surface area below 0.8 cmc, or above 1.2 cmc, decreases as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 49 publications
8
41
0
Order By: Relevance
“…When comparing the isotherms above the CMC in Fig. a, b, on average the equilibrium values were lower on the rough surface than the smooth surface, a result our group reported previously (Shi et al, ; Wu et al, ). This decrease in adsorption is caused by disruption of intermolecular tail‐tail interactions by surface roughness (Fragneto et al, ).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…When comparing the isotherms above the CMC in Fig. a, b, on average the equilibrium values were lower on the rough surface than the smooth surface, a result our group reported previously (Shi et al, ; Wu et al, ). This decrease in adsorption is caused by disruption of intermolecular tail‐tail interactions by surface roughness (Fragneto et al, ).…”
Section: Resultssupporting
confidence: 71%
“…Other studies have shown that gold and various other hydrophobic surfaces have supported the formation of bilayer films characteristic of a hydrophilic surface, although in some cases this was done purposefully by the addition of cosolutes (Fragneto et al, ; Gutig et al, ; Shi et al, ). The hydrophilic nature of the surface used in our experiments was found to be caused by the high concentration of oxygenated sites and the adsorption of halide ions, which have been reported previously by ours and other groups to create a negative charge on the surface (Knag et al, ; Mivehi et al, ; Wu et al, ). The gold surface provided by the manufacturer displays hydrophilic character even on the uncleaned surface, although further oxygenation and hydrophilicity is caused by the recommended cleaning procedure (RCA‐1 solution), which has been shown to increase the hydrophilicity of silicon as well (Bordes et al, ; Cademartiri and Ozin, ; Gutig et al, ; Hermansson et al, 1991).…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…The superhydrophobic coating causes a more substantial increase in the level of insertion loss to 8 dB and increased the bandwidth to 6.19 kHz. This can be interpreted as an additional dissipation of energy in air due to the high level of surface roughnesses [35]. All SH coated devices continued to operate with well behaved single mode resonance and good sensitivity.…”
Section: Investigation and Control Of The Wetting State Transition Ofmentioning
confidence: 88%